ANALISIS PERMALAN (FORECAST) PENJUALAN SEPEDA MOTOR HONDA PADA DEALER CAHAYA MOTOR INDAH MUARA TEMBESI - Jasasila Jasasila (Universitas Batanghari Jambi, 2018)
This study was conducted to determine the forecasting of Honda motorcycle sales at the Dealer Cahaya Motor Indah Muara Tembesi. The purpose of this study are: a) To know the development of Honda motorcycle sales at the Dealer Cahaya Motor Indah Muara Tembesi b) to know the forecasting of Honda motorcycle sales at the Dealer of Cahaya Motor Indah Muara Tembesi and c) To know the correct the right methode forecasting used Dealer Cahaya Indah Motor Muara Tembesi. The type of data used in this study is, primary data and secondary data with data sources obtained directly from Dealer Cahaya Indah Motor Muara Tembesi namely motorcycle sales data. Data collection method is done through literature study, From the data obtained and the analysis of the development of Honda motorcycle sales at dealer Cahaya Motor Indah Muara Tembesi within a period of four years ie 2012 to 2016 experiencing the fluctuating sales growth seen in 2013 there was a decline sales of 55.58%, for the year 2014 again a decline in sales from the previous year amounted to 11.76%, while in 2015 there was an increase of 26.59%, but in 2016 again sales decline by 24.57% from the previous year . The decrease of sales growth at Cahaya Motor Indah dealership is one of them caused by unstable community income, in general the source of income from the plantation sector (palm and rubber) which during the year of analysis also fluctuate in price, so it has influence on the demand of bicycle motorcycle. From the average sales volume growth of 1,025 units, then through the rationalization analysis peralaman is known forst sales volume in 2017 is 913 units, while the right method to be used by the Dealer Cahaya Motor Indah Muara Tembesi in forecasting is the method of Least Square and Moment Trend Method.Keywords: Method; Forecast; Sales